Meningkatkan Aktivitas Dan Hasil Belajar Peserta Didik Muatan PPKN Menggunakan Model Pelita Pada Kelas III SD - Nurmala Sari; Wahdah Refia Rafianti (CV. ITTC INDONESIA, 2023)
The problem in this study was the low activity and learning outcomes in class III students at UPTD SDN 1 Banyu Irang because the learning provided was only one-way, so students were less interested in the learning process and rarely expressed opinions. This study has the intent to describe teacher activities, student activities and analyze student learning outcomes in class III PPPKn content UPTD SDN 1 Banyu Irang. The type of research used was classroom action research (PTK) which was conducted in 4 meetings, this research was conducted in class III UPTD SDN 1 Banyu Irang consisting of 11 students. The type of data presented is data on teacher activity, student activity and student learning outcomes on PPPKn content obtained from observations, as well as data on student learning outcomes obtained from test results. The benchmark for research success is that 80% of students obtain or exceed the specified KKM, namely ≥70. Based on the data findings and results of this study, it can be concluded that teaching and learning activities by applying the PELITA (Problem Based Learning, Group Investigation, and Talking Stick) learning model are able to provide improvements to student learning activities and outcomes.